Politik Hukum Formalisasi Syariat Islam Di Indonesia - Muhammad Ainun Najib (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2017)
The implementation of Islamic law in Indonesia is strongly influenced by the interests of the authorities that cannot be separated from the poleksosbud context. To discuss it, the problem formulation is as follows: (1). How does thedynamics of political configuration between various governments in Indonesia have formalized the Islamic Shari'a? (2). What is the legal policy reality about the formalization of Islamic Shari'ah in Indonesia? Data from this study are traced and collected through literary sources, then analyzed inductively and comparably. This study concludes as follows. (1) Formalization of Islamic Shariah in Indonesia isexperiencing ups and downs. (2) Formalization of Islamic Shari'a was more influenced by relations between state and Islam. This is related to the character of Islamic struggle and the interests of the authorities.